× Close
Join the Ques10 Community
Ques10 is a community of thousands of students, teachers, and academic experts, just like you.
Join them; it only takes a minute
Sign up
Question: Verify Cayley-Hamilton theorem for following matrix and also find the following
0

$A^{-1} and A^4$

Subject: Applied Mathematics 4

Topic: Matrices

Difficulty: Medium

m4m(64) • 46 views
ADD COMMENTlink
modified 20 days ago  • written 20 days ago by gravatar for manasahegde234 manasahegde23410
0

Characteristic equation of A is $\mid A-\lambda I \mid=0$

$\lambda^3-6\lambda^2+[(4+4+4)-(1+1+1)]\lambda-\mid A \mid=0$

$\lambda^3-6\lambda^2+(12-3)\lambda-4=0$

$\lambda^3-6\lambda^2+9\lambda-4=0$

To verify Cayley-Hamilton Theorem, we need to prove that $A^3-6A^2-4I=0$

LHS=$A^3-6A^2+9A-4I$

$=$ $ \left[ {\begin{array}{cc} 22 & -21 & 21\ -21 & 22 & -21 \ 21 & -21 & 22\ \end{array} } \right] $-$6 \left[ {\begin{array}{cc} 6 & -5 & 5\\ -5 & 6 & -5 \\ 5 & -5 & 6\\ \end{array} } \right] $+$9 \left[ {\begin{array}{cc} 2 & -1 & 1\\ -1 & 2 & -1 \\ 1 & -1 & 2\\ \end{array} } \right]$ - $\left[ {\begin{array}{cc} 4 & 0 & 0\\ 0 & 4 & 0 \\ 0 & 0 & 4\\ \end{array} } \right] $

$=$ $ \left[ {\begin{array}{cc} 22 & -21 & 21\ -21 & 22 & -21 \ 21 & -21 & 22\ \end{array} } \right] $-$6 \left[ {\begin{array}{cc} 36 & -30 & 30\\ -30 & 36 & -30 \\ 30 & -30 & 36\\ \end{array} } \right] $+$9 \left[ {\begin{array}{cc} 18 & -9 & 9\\ -9 & 18 & -9 \\ 9 & -9 & 18\\ \end{array} } \right]$

$=$ $ \left[ {\begin{array}{cc} 22 & -21 & 21\ -21 & 22 & -21 \ 21 & -21 & 22\ \end{array} } \right] $-$6 \left[ {\begin{array}{cc} 6 & -5 & 5\\ -5 & 6 & -5 \\ 5 & -5 & 6\\ \end{array} } \right] $+$9 \left[ {\begin{array}{cc} 2 & -1 & 1\\ -1 & 2 & -1 \\ 1 & -1 & 2\\ \end{array} } \right]$ - $\left[ {\begin{array}{cc} 4 & 0 & 0\\ 0 & 4 & 0 \\ 0 & 0 & 4\\ \end{array} } \right] $

$=$ $\left[ {\begin{array}{cc} 0 & 0 & 0\ 0 & 0 & 0 \ 0 & 0 & 0\ \end{array} } \right] $= RHS $A^3-6A^2+9A-4I=0$ (1) Cayley-Hamilton Theorem verified. Now to find $A^{-1}$ and $A^4$. multiply (1) by $A{-1}$ we get, $A^{-1}(A^3-6A^2+9A-4I)=A^{-1}0$ $A^2-6A+9I-4A^{-1}=0$ $4A^{-1}=A^2-6A+9I$ $A^{-1}=\frac{1}{4}(A^2-6A+9I)$ $A^{-1}$=$\left[ {\begin{array}{cc} 6 & -5 & 5\\ -5 & 6 & -5 \\ 5 & -5 & 6\\ \end{array} } \right]$ $-6 \left[ {\begin{array}{cc} 2 & -1 & 1\\ -1 & 2 & -1 \\ 1 & -1 & 2\\ \end{array} } \right]$ + $\left[ {\begin{array}{cc} 9 & 0 & 0\\ 0 & 9 & 0 \\ 0 & 0 & 9\\ \end{array} } \right]] $

$\left[ {\begin{array}{cc} 6 & -5 & 5\\ -5 & 6 & -5 \\ 5 & -5 & 6\\ \end{array} } \right]$ -$ \left[ {\begin{array}{cc} 12 & -6 & 6\\ -6 & 12 & -6 \\ 6 & -6 & 12\\ \end{array} } \right]$ + $\left[ {\begin{array}{cc} 9 & 0 & 0\\ 0 & 9 & 0 \\ 0 & 0 & 9\\ \end{array} } \right]] $

=$\left[ {\begin{array}{cc} 3 & 1 & 1\\ 1 & 3 & 1 \\ -1 & 1 & 3\\ \end{array} } \right] $

To find $A^4$ multiply (1) by A

$A(A^3-6A^2+9A-4I)=A(0)$

$A^4-6A^3+9A^2-4A=0$

$A^4=6A^3-9A^2+4A$

=6$\left[ {\begin{array}{cc} 22 & -21 & 21\\ -21 & 22 & -21 \\ 21 & -21 & 22\\ \end{array} } \right]$ $-9 \left[ {\begin{array}{cc} 6 & -5 & 5\\ -5 & 6 & -5 \\ 5 & -5 & 6\\ \end{array} } \right]$ +4 $\left[ {\begin{array}{cc} 2 & -1 & 1\\ -1 & 2 & -1 \\ 1 & -1 & 2\\ \end{array} } \right] $

=$\left[ {\begin{array}{cc} 132 & -126 & 126\\ -126 & 132 & -126 \\ 126 & -126 & 132\\ \end{array} } \right]$ $-\left[ {\begin{array}{cc} 54 & -45 & 45\\ -45 & 54 & -45 \\ 45 & -45 & 54\\ \end{array} } \right]$ + $\left[ {\begin{array}{cc} 8 & -4 & 4\\ -4 & 8 & -4 \\ 4 & -4 & 8\\ \end{array} } \right] $

=$\left[ {\begin{array}{cc} 86 & -85 & 85\\ -85 & 86 & -85 \\ 85 & -85 & 86\\ \end{array} } \right] $

ADD COMMENTlink
written 20 days ago by gravatar for manasahegde234 manasahegde23410
Please log in to add an answer.


Use of this site constitutes acceptance of our User Agreement and Privacy Policy.